Crustal structures beneath the Saxonian Granulite Massif, the Ceske stredohori and the Doupovske hory Mts. based on the depth-recursive tomography - Novotny,M; Skacelova,Z.; Mlcoch,B. (Journal of Geosciences, 2010)
The P-wave velocity distribution, obtained recently by the depth-recursive tomography along the S01 refraction profile of the SUDETES 2003 seismic experiment, correlated fairly well with other geophysical results known in the area of the KTB deep drilling site. The S01 velocity model also provided a reliable velocity image of the upper and middle-crustal structures along the Eger Graben. In the present paper we will use the results of the depth-recursive tomography applied to the crossing S04 profile to derive a 3-D picture of structures near the S04 and S01 intersection.The NW-SE trending S04 profile starts in the Saxonian Granulite Massif and intersects the Eger Graben in the region of Altenberg-Teplice Caldera. The depth-recursive tomography, applied to the S04 profile, also produced a velocity model allowing together with the derived S01 velocities a reliable 3-D interpretation down to the depths of 15-20 km. Besides the P-wave velocities, gravity, aeromagnetic and petrophysical data support the presented geological interpretation. Using the velocity and gravity data we identified the subsurface granitic and ultrabasic bodies in wider surroundings of the Saxothuringian and Tepla-Barrandian contact zone and also possible magmatic centers for the Teplice-Altenberg Caldera as well as for the Doupovske hory and the Ceske stredohori volcanic complexes.
Keywords: Depth-recursive refraction tomography; SUDETES 2003 experiment; Bohemian Massif; Saxonian Granulite Massif; Altenberg-Teplice Caldera; Ceske stredohori volcanic complex; Doupovske hory volcanic complex